1982
DOI: 10.1002/jmv.1890090308
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of human coronavirus antibody in the population of southern iraq

Abstract: Sera from adults in Southern Iraq were collected during winter and screened by an enzyme-linked immunosorbent assay for the presence of antibodies to the two antigenic groups of human coronaviruses, the 229E and the OC43 groups: 91% of the sera had antibodies to at least one of the groups, whereas 4 and 5% of the sera had antibodies to only the 229E or OC43 groups, respectively. There was significant correlation between the levels of antibody to the 229E and OC43 group coronaviruses in these sera.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
18
1

Year Published

1983
1983
2014
2014

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 21 publications
6
18
1
Order By: Relevance
“…We have previously shown that mice from the specific pathogen-free unit of this Centre had no MHV 3 antibodies as determined by ELISA [3]. On immunization with denatured MHV 3 particles, IgG antibodies were detected against whole virus particles, and surface projection, membrane and RNP subcomponents.…”
Section: Resultsmentioning
confidence: 92%
See 4 more Smart Citations
“…We have previously shown that mice from the specific pathogen-free unit of this Centre had no MHV 3 antibodies as determined by ELISA [3]. On immunization with denatured MHV 3 particles, IgG antibodies were detected against whole virus particles, and surface projection, membrane and RNP subcomponents.…”
Section: Resultsmentioning
confidence: 92%
“…Virus preparations were disrupted with nonidet P40 and surface projection, membrane and RNP fractions were separated on sucrose density gradients as described previously [3,10]. Subcomponent fractions were shown to be uncontaminated with the other subcomponents by labelling their polypeptides with ~25I and analysing them on polyacrylamide gels [3,10]. Sera were collected from mice immunized with MHV 3 as previously described [3] with simple modifications.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations